Analisis Pengelolaan Fixed Asset Pada Disparpora Kabupaten Batang Berdasarkan PSAP No 7 (Studi Kasus Di Kawasan Objek Wisata Pantai Sigandu) - Jilma Dewi Ayu Ningtyas; Haris Syuhada (BALANCE: Economic, Business, Management and Accounting Journal, 2020)
ABSTRACT The financial statements of the government sector are prepared in accordance with the status of the agency. Based on observational data obtained at the Youth and Sports Tourism Office there are several fixed assets found in the Sigandu Beach Tourism Objects such as Buildings, Land, Equipment, Machines and Irrigation. This study wanted to find out the suitability of asset management managed by the asset section of the Office of Tourism and Youth Tourism as the agency responsible for managing fixed assets in the Sigandu Batang Beach Tourism Object with PSAP No. 7 regarding Accounting for fixed assets because the Office of Youth and Sports is a work unit under government policy. Data collection methods by interview, documentation and observation. Data analysis using descriptive qualitative. The conclusion of this study is that there are differences in the treatment of assets based on the Department of Youth Tourism and Sports with PSAP No. 7 which is point 5. The termination and disposal of fixed assets are not in accordance with PSAP No. 7 of 2010. Keywords       : Fixed Assets, PSAP no. 7, Public Sector Accounting ABSTRAK            Laporan keuangan sektor pemerintahan disusun sesuai dengan status instansi .Berdasarkan data observasi yang di peroleh di Dinas Pariwisata Kepemudaan Dan Olahraga ada beberapa aset tetap yang terdapat di Obyek Wisata Pantai Sigandu seperti Bangunan, Tanah, Peralatan, Mesin dan irigasi.  Penelitian ini ingin mengetahui kesesuian pengelolaan aset yang di kelola oleh bagian aset Kantor Dinas Pariwisata Kepemudaan Dan Olahraga selaku instansi yang bertanggung jawab atas pengelolaan aset tetap pada Obyek Wisata Pantai Sigandu Batang dengan PSAP No. 7 mengenai Akuntansi aset tetap karena Kantor Dinas Kepemudaan Dan Olahraga merupakan satuan kerja yang berada di bawah kebijakan pemerintahan. Metode Pengumpulan data dengan wawancara, dokumentasi dan observasi. Analisis data menggunakan deskriptif kualitatif. Kesimpulan pada penelitian ini adalah terdapat perbedaaan perlakuan aset berdasarkan Dinas Pariwisata Kepemudaan dan Olahraga dengan PSAP No. 7 yaitu pada poin 5. Penghentian dan pelepasan aset tetap  tidak sesuai dengan PSAP No. 7 Tahun 2010.Kata Kunci     : Aset Tetap, PSAP No. 7, Akuntansi Sektor Publik